Surface mass balance and stable oxygen isotope ratios from shallow firn cores on Fimbulisen, East Antarctica - Schlosser, Elisabeth; Anschütz, Helgard; Isaksson, Elisabeth; Martma, T; Divine, Dmitry; Nøst, Ole Anders (Annals of Glaciology, 2012)
The mass balance of Antarctica is one of the crucial factors for determining sea-level change in a warming climate. The marginal zones of the continent, namely the ice shelves, are most sensitive to climate change. During the 2009/10 austral summer an extensive glaciological field campaign was carried out on Fimbulisen, an ice shelf in East Antarctica, to investigate its recent surface mass balance. Shallow (10–18 m) firn cores were drilled and accumulation rates and stable-isotope ratios determined. For firn-core dating, two different methods were compared: (1) seasonal variations of stable oxygen isotope ratios (δ18O), and (2) dielectric profiling, including using the volcanic eruptions of Pinatubo, Philippines (1991), and El Chichόn, Mexico (1982), as time markers. The mean annual accumulation for the period 1992–2009 ranges from 298 to 349 mmw.e. a–1. The interannual variability at the drilling sites is >30%. Accumulation rates show a weak decreasing trend during the past 20–30 years, which is statistically significant only for one of the cores. Stable-isotope ratios were compared to the snowfall temperature of Neumayer station. Neither the temperatures nor the δ18O values show any trend for the investigated time period.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

Recent climate tendencies on an East Antarctic ice shelf inferred from a shallow firn core network - Schlosser, Elisabeth; Anschütz, Helgard; Divine, Dmitry; Martma, Tõnu; Sinisalo, Anna; Altnau, Sebastian; Isaksson, Elisabeth (Journal of Geophysical Research: Atmospheres, 2014)
Nearly three decades of stable isotope ratios and surface mass balance (SMB) data from eight shallow firn cores retrieved at Fimbul Ice Shelf, East Antarctica, in the Austral summers 2009–2011 have been investigated. An additional longer core drilled in 2000/2001 extends the series back to the early eighteenth century. Isotope ratios and SMB from the stacked record of all cores were also related to instrumental temperature data from Neumayer Station on Ekström Ice Shelf. Since the second half of the twentieth century, the SMB shows a statistically significant negative trend, whereas the δ18O of the cores shows a significant positive trend. No trend is found in air temperature at the nearest suitable weather station, Neumayer (available since 1981). This does not correspond to the statistically significant positive trend in Southern Annular Mode (SAM) index, which is usually associated with a cooling of East Antarctica. SAM index and SMB are negatively correlated, which might be explained by a decrease in meridional exchange of energy and moisture leading to lower precipitation amounts. Future monitoring of climate change on the sensitive Antarctic ice shelves is necessary to assess its consequences for sea level change.
Keywords: Antarktis; brehylle; geofysikk; geologi; glasiologi; havnivåstigning; isbrem; isshelf; klimaendringer; meteorologi; stabile isotoper

Revisiting sites of the South Pole Queen Maud Land Traverses in East Antarctica: Accumulation data from shallow firn cores - Anschütz, Helgard; Müller, Karsten; Isaksson, Elisabeth; McConnell, Joseph R.; Fischer, Helmut; Miller, Heinz; Albert, Mary; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2009)
[1] Ground-based accumulation measurements are scarce on the high East Antarctic plateau, but highly necessary for model validation and the interpretation of satellite data for the determination of Antarctic mass balance. Here, we present accumulation results obtained from four shallow firn cores drilled in the Antarctic summer season 2007/2008. The cores were drilled along the first leg of the Norwegian-US IPY traverse through East Antarctica, visiting sites like Plateau Station and Pole of Relative Inaccessibility that have been covered by the South Pole Queen Maud Land Traverses (SPQMLT) in the 1960s. Accumulation has been determined from volcanic chronology established from the conductivity records measured by dielectric profiling (DEP). The Tambora 1815/unknown 1809 double peak is clearly visible in the conductivity data and serves as a reliable time marker. Accumulation rates averaged over the period 1815–2007 are in the range of 16 to 32 kg m−2 a−1, somewhat lower than expected from the SPQMLT data. The spatial pattern is mainly influenced by elevation and continentality. Three of the firn cores show a decrease of more than 20% in accumulation for the time period 1815–2007 in relation to accumulation rates during the period 1641–1815. The spatial representativity of the firn cores is assessed by ground-penetrating radar, showing a rather smoothly layered pattern around the drill sites. Validation of the DEP results is utilized by comparison with chemistry data, proving the validity of the DEP method for dating firn cores. The results help understanding the status of the East Antarctic ice sheet and will be important for e.g. future model-derived estimates of the mass balance of Antarctica.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbreer; vulkaner

Variation of accumulation rates over the last eight centuries on the East Antarctic Plateau derived from volcanic signals in ice cores - Anschütz, Helgard; Sinisalo, Anna; Isaksson, Elisabeth; McConnell, Joseph R; Hamran, Svein Erik; Bisiaux, M M; Pasteris, Daniel R; Neumann, Thomas; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2011)
Volcanic signatures in ice-core records provide an excellent means to date the cores and obtain information about accumulation rates. From several ice cores it is thus possible to extract a spatio-temporal accumulation pattern. We show records of electrical conductivity and sulfur from 13 firn cores from the Norwegian-USA scientific traverse during the International Polar Year 2007–2009 (IPY) through East Antarctica. Major volcanic eruptions are identified and used to assess century-scale accumulation changes. The largest changes seem to occur in the most recent decades with accumulation over the period 1963–2007/08 being up to 25% different from the long-term record. There is no clear overall trend, some sites show an increase in accumulation over the period 1963 to present while others show a decrease. Almost all of the sites above 3200 m above sea level (asl) suggest a decrease. These sites also show a significantly lower accumulation value than large-scale assessments both for the period 1963 to present and for the long-term mean at the respective drill sites. The spatial accumulation distribution is influenced mainly by elevation and distance to the ocean (continentality), as expected. Ground-penetrating radar data around the drill sites show a spatial variability within 10–20% over several tens of kilometers, indicating that our drill sites are well representative for the area around them. Our results are important for large-scale assessments of Antarctic mass balance and model validation.
Keywords: Antarktis; akkumulasjon; geovitenskap; glasiologi; innlandsis; iskjerner; klimatologi

Surface mass balance on Fimbul ice shelf, East Antarctica: Comparison of field measurements and large-scale studies - Sinisalo, Anna; Anschütz, Helgard; Aasen, Anne Tårånd; Langley, Kirsty; von Deschwanden, Angela; Kohler, Jack; Matsuoka, Kenichi; Hamran, Svein- Erik; Øyan, Mats-Jørgen; Schlosser, Elisabeth; Hagen, Jon Ove; Nøst, Ole Anders; et al. (Journal of Geophysical Research: Atmospheres, 2013)
Many challenges remain for estimating the Antarctic ice sheet surface mass balance (SMB), which represents a major uncertainty in predictions of future sea-level rise. Validating continental scale studies is hampered by the sparse distribution of in situ data. Here we present a 26 year mean SMB of the Fimbul ice shelf in East Antarctica between 1983–2009, and recent interannual variability since 2010. We compare these data to the results of large-scale SMB studies for similar time periods, obtained from regional atmospheric modeling and remote sensing. Our in situ data include ground penetrating radar, firn cores, and mass balance stakes and provide information on both temporal and spatial scales. The 26 year mean SMB on the Fimbul ice shelf varies between 170 and 620 kg m−2 a−1 giving a regional average value of 310 ± 70 kg m−2 a−1. Our measurements indicate higher long-term accumulation over large parts of the ice shelf compared to the large-scale studies. We also show that the variability of the mean annual SMB, which can be up to 90%, can be a dominant factor in short-term estimates. The results emphasize the importance of using a combination of ground-based validation data, regional climate models, and remote sensing over a relevant time period in order to achieve a reliable SMB for Antarctica.
Keywords: Dronning Maud Land; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi